METABOLIC SYNDROME AMONG DOCTORS: A PILOT STUDY FROM ODISHA - Manjareeka, Magna; Mishra, Soumya; Nayak, Prakash K; Patro, Shubhransu; Mishra, Jayanti; Dash, Suresh C (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was planned to assess the prevalence of metabolic syndrome (MetS) among doctors of Bhubaneswar. Methods: A cross-sectional, single-centered observational study was conducted among doctors over a period of 8 months after clearance from Institutional Ethical Committee. All consented participants were subjected to anthropometric measurements and physical examination. Fasting plasma glucose and complete lipid profile were estimated using standard procedures after 12 h of overnight fast. MetS was defined according to the Modified National Cholesterol Education Program-Adult Treatment Panel III criteria for MetS screening. Results: Among 170 participants (males - 117 and females - 53), 64 (37.65%) were with MetS. Prevalence of same was higher in males (41.9%) than females (28.3%). The younger doctors (â‰¤40 years) had more prevalence of MetS compared to the elderly (>40 years) doctors (41 [39.8%] vs. 23 [34.3%]). In the males, high blood pressure was the major contributor to the prevalence of MetS followed by low high-density lipoproteins-cholesterol (HDL-C) and high triglyceride values. However, in females, low HDL-C and greater waist circumference contributed the maximum to MetS. Conclusion: In the present study, the young male doctors have a greater prevalence of MetS than the older and the females. MetS is still a significant public health problem in the educated population including those of doctors, especially the younger ones. Â 